The Role of Thyroid Hormones in Hepatocyte Proliferation and Liver Cancer - Gionfra, Fabio; De Vito, Paolo; Pallottini, Valentina; Lin, Hung-Yun; Davis, Paul J.; Pedersen, Jens Z.; Incerpi, Sandra (Frontiers in Endocrinology, 2019)
Thyroid hormones T3 and T4 (thyroxine) control a wide variety of effects related to development, differentiation, growth and metabolism, through the interaction with nuclear receptors. But thyroid hormones also produce nongenomic effects which typically start at the plasma membrane and are mediated mainly by integrin αvβ3, although also other receptors such as TRα and TRβ are able to elicit nongenomic responses. In the liver these effects of thyroid hormones appear to be particularly important. The liver is able to regenerate, but it is subject to pathologies that may lead to cancer, such as fibrosis, cirrhosis and non-alcoholic fatty liver disease. In addition, cancer cells undergo a reprogramming of their metabolism resulting in drastic changes such as aerobic glycolysis instead of oxidative phosphorylation. As a consequence the pyruvate kinase isoform M2, the rate-limiting enzyme of glycolysis, is dysregulated, and this is considered an important factor in tumorigenesis. Redox equilibrium is also important, in fact cancer cells give rise to production of more reactive oxygen species (ROS) than normal cells. This increase may favor the survival and propagation of cancer cells. We here evaluate the possible mechanisms involving the plasma membrane receptor integrin αvβ3 that may lead to cancer progression. The study of the diseases that affect the liver and their experimental models may help to unravel the cellular pathways mediated by integrin αvβ3 that can lead to liver cancer. Inhibitors of integrin αvβ3 might represent a future therapeutic tool against liver cancer. We also include information on the possible role of exosomes in liver cancer, as well as on recent strategies such as organoids and spheroids that may provide a new tool for research, drug discovery, and personalized medicine.